2020
DOI: 10.29025/2079-6021-2020-4-104-115
|View full text |Cite
|
Sign up to set email alerts
|

Buzzwords as an example of interlingual lacunarity in various kinds of professional discourse (based on the English language material)

Abstract: The article is focused on the analysis of structural-semantic features of buzzwords and relating to them problem of interlingual lacunarity in two kinds of professional discourse – business and political-legal discourse. Buzzwords are understood as a special category of lexical units which emerge die to the need of nominating new culture-specific elements, tendencies and trends, as well as attaching novelty to existing in the language phenomena. The study relevance is stipulated by the common understanding tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Studies of semantic lexical gaps in business and legal discourse [21,22] showed that they may be viewed as a way of transmitting national and cultural specifics of the language; they include a number of idioms, phraseological units, proverbs and sayings [23] Besides, they reflect differences in values between the two linguocultures [24].…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Studies of semantic lexical gaps in business and legal discourse [21,22] showed that they may be viewed as a way of transmitting national and cultural specifics of the language; they include a number of idioms, phraseological units, proverbs and sayings [23] Besides, they reflect differences in values between the two linguocultures [24].…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%